TI_GERICHTE 52.2019.196 vom 30. Dezember 2020 , Licenza edilizia in sanatoria per la formazione di un accesso veicolare sterrato - TI Tribunale d'appello (2020)
Licenza edilizia in sanatoria per la formazione di un accesso veicolare sterrato